2022
DOI: 10.3390/f13060842
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Ditch Cleaning Has No Impact on the Carbon and Greenhouse Gas Balances in a Recent Forest Clear-Cut in Boreal Sweden

Abstract: Ditch cleaning (DC) is increasingly applied to facilitate forest regeneration following clear-cutting in Fennoscandinavia. However, its impact on the ecosystem carbon and greenhouse gas (GHG) balances is poorly understood. We conducted chamber measurements to assess the initial DC effects on carbon dioxide (CO2) and methane (CH4) fluxes in a recent forest clear-cut on wet mineral soil in boreal Sweden. Measurements were conducted in two adjacent areas over two pre-treatments (2018/19) and two years (2020/21) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
0
8
1
Order By: Relevance
“…The mechanism of the delayed herbaceous vegetation development following DC in our study remains uncertain, however, it is to be noted that the upper part of the soil profile at the site was relatively dry with a mean WTL of − 54 to − 56 cm in all our sampling locations in the two sampling years (Table A.2) which is in contrast to previous studies in boreal mineral soil forests (e.g. Tong et al, 2022) and drained peatland forests with shallower mean WTLs of − 30 to − 40 cm (e.g. Leppä et al, 2020;Lohila et al, 2011;Ojanen and Minkkinen, 2019).…”
Section: Initial Effects On Spatio-temporal Variations Of Ghg Fluxes ...contrasting
confidence: 87%
See 2 more Smart Citations
“…The mechanism of the delayed herbaceous vegetation development following DC in our study remains uncertain, however, it is to be noted that the upper part of the soil profile at the site was relatively dry with a mean WTL of − 54 to − 56 cm in all our sampling locations in the two sampling years (Table A.2) which is in contrast to previous studies in boreal mineral soil forests (e.g. Tong et al, 2022) and drained peatland forests with shallower mean WTLs of − 30 to − 40 cm (e.g. Leppä et al, 2020;Lohila et al, 2011;Ojanen and Minkkinen, 2019).…”
Section: Initial Effects On Spatio-temporal Variations Of Ghg Fluxes ...contrasting
confidence: 87%
“…To our knowledge, there is only one published study to date that explored DC effects on the forest GHG balance which was carried out in a forest clear-cut on wet mineral soil in boreal Sweden (Tong et al, 2022). This study reported insignificant effects of DC on C and GHG balances and vegetation development, despite changes in WTL due to DC.…”
Section: Total Ghg Balance Following DCmentioning
confidence: 87%
See 1 more Smart Citation
“…In agreement with our findings, relatively stable RH rates were also observed in a nutrient‐limited (C:N ratio = 29) Scots pine chronosquence in hemiboreal Estonia (Uri et al, 2022 ) and in a synthesis study of RH in the boreal region (Pregitzer & Euskirchen, 2004 ). It is noteworthy, however, that our study lacks NEP data from the first few years after harvest during which considerably larger emissions have been reported by other studies conducted in boreal (Tong, Nilsson, et al, 2022 ) and hemiboreal (Tong, Nilsson, Sikström, et al, 2022 ; Vestin et al, 2020 ) clear‐cut sites.…”
Section: Discussionmentioning
confidence: 59%
“…To argue for his concern, Lindroth (2023) complemented our dataset with one additional data point representing emissions of 610 g C m −2 year −1 during the second post‐harvest year in another boreal clear‐cut site (Tong et al, 2022). He then re‐fitted the NEP trajectory through the extended dataset and finds that SST, CCP, and OCS shifted from the 8, 18, and 138 years reported in Peichl et al (2023) to 16, 39, and 155 years, respectively.…”
Section: Figurementioning
confidence: 99%